2011
DOI: 10.1111/j.1945-5100.2010.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

δ18O and chemical composition of Libyan Desert Glass, country rocks, and sands: New considerations on target material

Abstract: Abstract-Oxygen isotope and chemical measurements were carried out on 25 samples of Libyan Desert Glass (LDG), 21 samples of sandstone, and 3 of sand from the same area. 18 O values compatible with the LDG values suggesting that the modern surface sand inherited quartz from the target material. This hypothesis fits previous findings of lechatelierite and baddeleyite in these materials. As the age of the parent material reported in previous studies is Pan-African, we measured the d18 O values of bulk rock and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
(33 reference statements)
8
15
0
Order By: Relevance
“…We also observed distorted layers of hollow vesiculated silica glass tube-like features, similar to some LDG samples (Fig. 12), which are attributed to relic sedimentary bedding structures in the sandstone precursor (39). The Abu Hureyra tubular textures may be relic structures of thin-bedded chert that occurs within the regional chalk deposits.…”
Section: Sem or Eds Analyses To Determine Whether Their Spherules Aresupporting
confidence: 74%
“…We also observed distorted layers of hollow vesiculated silica glass tube-like features, similar to some LDG samples (Fig. 12), which are attributed to relic sedimentary bedding structures in the sandstone precursor (39). The Abu Hureyra tubular textures may be relic structures of thin-bedded chert that occurs within the regional chalk deposits.…”
Section: Sem or Eds Analyses To Determine Whether Their Spherules Aresupporting
confidence: 74%
“…The rare earth element abundance patterns are indicative of a sedimentary precursor rock, and the trace element abundances and ratios are in agreement with an upper crustal source. In agreement with the strontium and neodymium isotopic data, which suggest a Pan-African age of the parent material for the LDG, Longinelli et al (2011) measured the d 18 O values of bulk rock and quartz from intrusives of Pan-African age and the results obtained were compatible with their values obtained for LDG samples. This was confirmed by Koeberl (2000) in an osmium isotopic study.…”
Section: Libyan Desert Glasssupporting
confidence: 86%
“…; Longinelli et al. ). Various field investigations have shown that their strewn field covers a circular area of about 21 km diameter (Barakat et al.…”
Section: Introductionmentioning
confidence: 99%
“…Svetsov and Watson (), Boslough and Crawford (), and Longinelli et al. () proposed that LDG did not originate from a meteorite impact, but from a comet airburst. Finally, using various isotopic compositions, Schaaf and Müller‐Sohnius () and Longinelli et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation